PENGARUH EDUKASI SIAGA BENCANA MELALUI MEDIA VIDEO DAN BOOKLET BAHASA DAERAH TERHADAP KESIAPSIAGAAN ANAK DALAM MENGHADAPI BENCANA GEMPA BUMI DI LOMBOK - Ririnisahawaitun Ririnisahawaitun; Dwi Wirastri; Dina Alfiana Ikhwani (LPSDI Bina Patria, 2022)
Background: North Lombok is the district with the highest number of earthquake disaster victims. Children are a vulnerable group because of their lack of ability to save themselves. Children are anxious about a possible recurrence of disasters, separating from parents, and fearful for their own safety. Children are required to improve their preparedness for earthquakes, which can be improved by providing education using video- and local language booklets. Purpose: To determine the effect of disaster preparedness education through video- and local language booklets on children's preparedness in facing earthquakes. Methods: This study was a quasi-experimental study, with a pretest-posttest control group design. The research sample was taken by cluster random sampling, which was divided into a control group (education with media booklet) of 66 children and an experimental group (education using video-media) of 69 children. Results: There were differences in the control group and the experimental group after being given education (p value in the control group and the experimental group = 0.000 for each). In exprerimental group showed that preparedness differences is higher than children preparednes in control group (mean of control group = 11.7397; mean of experimental group = 12.9139). Conclusion: Increased preparedness was higher in children who were given education with video compared with children who were given education with booklet.